DOMESTIC, PRIVATE AND PUBLIC SPACE IN WOMEN FROM THE POPULAR SECTORS OF LIMA - LUQUE VELARDE, Martha (2021)
The article analyzes, from a gender perspective, the social relations established by women from the popular sectors of Lima in the domestic, private and public spaces. The social practices of popular women in the life of the home are exposed, describes the construction of their own space and examines their participation in the work and popular organizations.